Employment Opportunities for Degree Holder in the Post-Pandemic Era: Basis for Manpower Recruitment and Selection Policy - Li, DBA, Hongfei (International Journal of Scientific Research and Management (IJSRM), 2024)
Since January 2020, a new coronavirus has triggered a global outbreak. As the global economy has expanded outside China, it has grown increasingly unstable and unpredictable, making it challenging to find job and thrive economically and socially. As a result, graduates faced uncertainty in the employment market, particularly during the outbreak. "Employment" was used more than any other phrase in the government's 2020 strategy report. The study advocated for a concerted effort to sustain and grow employment, as well as a tried-and-true framework for stability, employment, and social security. Furthermore, employment was the main goal shared by the "six stable" and "six guaranteed" important works after the pandemic of 2021.The pandemic impacted students who had yet to apply to graduate school. Parallel to this, contemporary professional progression entailed some degree of uncertainty and unpredictability, making career changes necessary for personal development. Professional adaptation, defined as "the individual's preparedness and coping resources when confronting the uncertainty and complexity brought on by career transformation," has the potential to have a substantial influence on professional growth. Adaptability to changing situations and possibilities was essential for professional success.Academics provided proof that adaptability was necessary for professional achievement. Furthermore, to address the issue of employment, government and private sector job recruiting practices must be re-evaluated in order to tackle long-term unemployment problems. To fight unemployment, management must focus on job creation and vocational training, as well as enhancing the work environment, growing employment, and optimizing the economic structure. In addition, several research found that when respondents were categorized based on their profile, their estimate of the effect of adopting human resource management remained consistent. As a result, the researcher performed a study to better understand the issue and provide recommendations for potential remedies.